Control of the Effective Free-Energy Landscape in a Frustrated Magnet by a Field Pulse - Wan, Yuan; Moessner, Roderich (Physical review letters, 2017)
Thermal fluctuations can lift the degeneracy of a ground state manifold, producing a free-energy landscape without accidentally degenerate minima. In a process known as order by disorder, a subset of states incorporating symmetry breaking may be selected. Here, we show that such a free-energy landscape can be controlled in a nonequilibrium setting as the slow motion within the ground state manifold is governed by the fast modes out of it. For the paradigmatic case of the classical pyrochlore XY antiferromagnet, we show that a uniform magnetic field pulse can excite these fast modes to generate a tunable effective free-energy landscape with minima at thermodynamically unstable portions of the ground state manifold.